Factor Analysis of Arabic Writing Errors in MI and Equivalent Students - Gamal, Muhammad (Al-Muyassar: Journal of Arabic Education, 2024)
This research aims to analyze Arabic writing errors that often occur in elementary school students when learning Arabic.  In this research, the objects of research were several Madrasah Ibtidayah students.  The aim of this analysis is to identify the factors that cause errors in writing Arabic letters in elementary school students.  This research method uses a form of descriptive research with a qualitative approach. Descriptive research aims to define, obtain, analyze and interpret everything that exists and is applicable with the analysis consisting of collecting data on common mistakes made by students when writing Arabic letters.  This research was conducted at 5 MI with 9 students.  The results of the analysis show that there are several main factors that cause errors in writing Arabic, including a lack of understanding of Arabic grammar rules.  Keywords: Arabic;  Writing;  Error Factor.